Understanding the Role of Social Determinants in Shaping Chronic Disease Outcomes: A Comprehensive Review - Alabbas, Fahad Mahdi Abdullah; Al Abbas, Ali Merzah; Alabbas, Hussain Mesfer; Alabbas, Hamad Merzah; Albaqami, Qidan Ayidh Qidan; Al Rashdi, Abdullah Menwer; Almakrami , Hussain Abdullah Hussain; Al-Khudhayr, Abdullah Bin Mohammed Bin Abdullah; Almakrami , Mansour Abdullah Ali; Al Jamhour , Abdullah Mana Saeed (Journal of Ecohumanism, 2024)
This review explores the influence of social determinants of health (SDH) on chronic disease outcomes, focusing on the interconnected roles of socioeconomic status, physical environment, community context, education, healthcare access, and behavioral determinants. Chronic diseases—such as cardiovascular disease, diabetes, and respiratory conditions—pose a significant public health challenge, with social determinants increasingly recognized as critical factors in shaping their prevalence, progression, and management. This review synthesizes findings from recent studies to elucidate how SDH create disparities in chronic disease outcomes, particularly among marginalized populations. We examine mechanisms linking SDH to chronic disease, including biopsychosocial and behavioral pathways, and discuss implications for public health interventions and policy-making. Addressing these social determinants through comprehensive public health strategies could help reduce the burden of chronic diseases, improve health equity, and support healthier communities.